ANALISIS MISKONSEPSI HUKUM NEWTON GERAK LURUS UNTUK MENGETAHUI TINGKAT PEMAHAMAN SISWA MENGGUNAKAN FOUR TIER BERBASIS LOCAL WISDOM - Ayu Daynuari, Mellina; Stiaji, Bayu (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
This study aims to analyze the level of understanding of students using the four tier method to find out how far the level of understanding of the questions given to students in Newton's law of straight motion material. This research was conducted to map out how well students understand the concept of Newton's law of straight motion with traditional games and local wisdom. This research method uses literature study. Research data were obtained from 14 articles selected through abstract reading, then reading the contents of the articles via Google Scholar and Mendeley indicated from 2018 to 2022. The selected articles have the same type of four-tier test diagnostic instrument with Newton's law of straight motion in students. SMA and articles that integrate local wisdom in Newton's laws of straight motion. The cause of misconceptions about physics in the subject of Newton's law in SMA/MA is a lack of conceptual understanding of the material provided and there is an incompatibility of the questions with the material provided. The development of a four-tier diagnostic test instrument is a method for detecting misconceptions in physics that is often developed in research, because it is considered more effective and more accurate in detecting misconceptions in students, especially in Newton's law of straight motion.